Tracking snacking in real time: Time to look at individualised patterns of behaviour. Issue 3 (September 2019) - Allan, Julia; McMinn, David; Powell, Daniel
Background: Identifying when and where people overeat is important for intervention design, yet little is known about how unhealthy behaviours unfold in real life. Aim: To track the activities, social contexts and locations that co-occur with unhealthy snacking. Methods: Sixty-four adults (49F, mean age = 38.6 years) used electronic diaries to record snacking, location, social context and current activity every waking hour over 7 days. The proportion of snacking episodes that co-occurred with each location/activity/context was calculated by group and individual. Results: Over the group, snacking was most frequent whilst socialising (19.9% of hours spent socialising) or using the TV/computer (19.7%), when with friends (16.7%) and when at home (15.3%). All intra-class correlation statistics for cued behaviour were low, indicating the importance of within-person variability. There were marked individual differences between people in what constituted a 'typical' context for snacking. Conclusions: People show substantial differences in the contexts in which they snack. Tailoring interventions to these individual patterns of behaviour may improve intervention efficacy.